The Goal and Path of Post-traumatic Stress Disorder Intervention in College Students from the Perspective of Positive Psychology - Xia, Yu (Journal of Theory and Practice of Contemporary Education, 2023)
Positive psychology explores the significance of psychological construction from the positive aspect of human temperament, and attaches importance to the positive experience of human emotions. Nowadays, college students may have more or less negative emotions, and this discipline can precisely improve their positive and optimistic levels and happiness index from a reverse perspective. This article mainly analyzes the goal and path of post-traumatic irritability disorder intervention from the perspective of positive psychology.